2013
DOI: 10.6007/ijarafms/v3-i3/42
|View full text |Cite
|
Sign up to set email alerts
|

The Study of University Professors' Financial Literacy

Abstract: Industrial revolution, economic crises, and facilitation and expansion of global communication have increased the volume of transactions and management complexity. This complexity has led to a situation that people are not able to simply make good financial decisions in their business and personal life. With the financial and economic activities becoming more difficult, countri es have concluded that whole the public essentially need to be trained about financial issues. The study of financial literacy of popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…, 2013; Goyal and Kumar, 2021; Guiso and Jappelli, 2005; Volpe et al. , 1996) but in some cases, a positive impact has been observed (Cude, 2010; Nayebzadeh et al ., 2013) or insignificant association (Kadoya and Khan, 2020; Loke, 2017; Ramakrishnan, 2012). Education also plays a crucial role in financial literacy as more educated people have higher chances of getting higher financial literacy (Agarwalla et al.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…, 2013; Goyal and Kumar, 2021; Guiso and Jappelli, 2005; Volpe et al. , 1996) but in some cases, a positive impact has been observed (Cude, 2010; Nayebzadeh et al ., 2013) or insignificant association (Kadoya and Khan, 2020; Loke, 2017; Ramakrishnan, 2012). Education also plays a crucial role in financial literacy as more educated people have higher chances of getting higher financial literacy (Agarwalla et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Whereas (Fatoki, 2014;Ramakrishnan, 2012) did not observe any significant impact of education. Income has a positive impact on financial literacy (Agarwalla et al, 2013;Cameron et al, 2013;Cude, 2010;Hamid and Loke, 2021;Kadoya and Khan, 2020;Loke, 2017;Lusardi et al, 2010) but some studies did not found any link (Fatoki, 2014;Nayebzadeh et al, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations